Brooklyn Before : Photographs, 1971-1983 - Van Haaften, Julia; Robbins, Tom (Journalist) (Book collections on Project MUSE., 2018)
Before Brooklyn rose to international fame there existed a vibrant borough of neighborhoods rich with connections and traditions. During the 1970s and 1980s, photographer Larry Racioppo, a South Brooklynite with roots three generations deep, recorded Brooklyn on the cusp of being the trendy borough we know today. In Brooklyn Before Racioppo lets us see the vitality of his native Brooklyn, stretching from historic Park Slope to the beginnings of Windsor Terrace and Sunset Park. His black and white photographs pull us deep into the community, stretching our memories back more than forty years and teasing out the long-lost recollections of life on the streets and in apartment homes. Racioppo has the fascinating ability to tell a story in one photograph and, because of his native bona fides, he depicts an intriguing set of true Brooklyn stories from the inside, in ways that an outsider simply cannot. On the pages of, Brooklyn Before the intimacy and roughness of life in a working-class community of Irish American, Italian American, and Puerto Rican families is shown with honesty and insight. Racioppo's 128 photographs are paired with essays from journalist Tom Robbins and art critic and curator Julia Van Haaften. Taken together, the images and words of Brooklyn Before return us to pre-gentrification Brooklyn and immerse us in a community defined by work, family, and ethnic ties.